Fiscal Reform in the People's Republic of China: Current Issues and Future Agenda - Toshiki Kanamori (Asian Development Bank Institute (ADBI), 2004)
In recent years, economists and policymakers have given much greater attention to fiscal reform in the PRC. This reflects the fact that after the Asian financial crisis the fiscal balance of the PRC government rapidly worsened. Second, the PRC economy as a whole has been moving in a more market-oriented direction since its accession to the World Trade Organization (WTO). The current agenda for fiscal reform includes the low level of fiscal revenue relative to GDP, the tax-sharing scheme between central and local governments, preferential tax treatment for foreign-invested companies, and the tax structure and tax collection for individuals, particularly the wealthy. The agenda for future fiscal reform in the PRC involves first building a public finance structure that conforms to the market-oriented macroeconomic system that will emerge from ongoing reforms, and the PRC's opening-up policy. The second agenda is the strengthening of fiscal instruments as a national macroeconomic policy for achieving stable and sustainable economic growth, and a policy for achieving social welfare and justice.
hdl:11540/4160
Keywords: 330; Finanzreform; China